2011
DOI: 10.1021/jm101199t
|View full text |Cite
|
Sign up to set email alerts
|

Selective Depletion of Mutant p53 by Cancer Chemopreventive Isothiocyanates and Their Structure−Activity Relationships

Abstract: Isothiocyanates (ITCs) derived from cruciferous vegetables induce apoptosis in cancer cells. We demonstrate that certain naturally-occurring ITCs selectively deplete mutant p53, but not the wild type, and do so via a transcription-independent mechanism. Direct p53 binding followed by conformational changes appears to be a mechanism by which mutant p53 is depleted. Structure-activity relationship studies (SARs) using naturally-occurring and synthetic ITCs show that depletion is influenced by the ITC side chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 12 publications
8
66
0
Order By: Relevance
“…Further, PEITC has been shown to have a significant hormetic protective effect due to its ability to induce the expression of various detoxification enzymes and antioxidant molecules, which may contribute to its chemopreventive activity (6). The potent anticancer activity of PEITC is likely attributed to its multiple mechanisms of action, including abrogation of the GSH system, direct binding to certain proteins that are important for cell survival, inducing phosphorylation of p66(Shc), and inhibition of enzymes such as GPX and proteasomes (30,36,41,45). In our study, we found that 10 lM PEITC dramatically inhibited respiration by > 80% in HL-60 and Raji cells with only a 3-h treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, PEITC has been shown to have a significant hormetic protective effect due to its ability to induce the expression of various detoxification enzymes and antioxidant molecules, which may contribute to its chemopreventive activity (6). The potent anticancer activity of PEITC is likely attributed to its multiple mechanisms of action, including abrogation of the GSH system, direct binding to certain proteins that are important for cell survival, inducing phosphorylation of p66(Shc), and inhibition of enzymes such as GPX and proteasomes (30,36,41,45). In our study, we found that 10 lM PEITC dramatically inhibited respiration by > 80% in HL-60 and Raji cells with only a 3-h treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PEITC may also interact with 26S and 20S proteasomes and inhibits the enzyme activity (30). A recent study suggests that this compound seems to bind to mutant p53 and cause its conformational change, thus leading to its depletion (41). Interestingly, PEITC induces phosphorylation of p66Shc, which may translocate to mitochondria and enhance reactive oxygen species (ROS) production and DNA fragmentation (45).…”
Section: Innovationmentioning
confidence: 99%
“…A plethora of pre-clinical studies suggest a strong anticancer activity of PEITC. [15][16][17][18][19][20][21][22][23][24] Phase I and II clinical trials are also in progress to test PEITC against lung cancer and leukemia. 25 Hence we evaluated the effects of PEITC on tumor-modulatory immune cells circulating in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…Individual lysine residues within functional protein pockets are also susceptible to modification by electrophilic small molecules, including natural products, such as Wortmannin 18 , which targets a lysine in the active sites of PI3K kinases, activated esters that react with a lysine in transthyretin (TTR) 19 , and boronic acid carbonyl antagonists of the apoptosis regulatory protein MCL-1 13 . Additional electrophiles that have been shown to react with proteinaceous lysine residues include dichlorotriazines 20,21 , imidoesters 22 , 2-acetyl- or 2-formyl-benzeneboronic acids 13,23 , isothiocyanates 24,25 , pyrazolecarboxamidines 26,27 , sulfonyl fluorides 28,29 , and vinyl sulfonamides 30 .…”
mentioning
confidence: 99%